Analysis of Payment Delay in Road Construction Projects: The Case Road Division Surkhet, Nepal - Paudel, Top Narayan; Bhattarai, Subash Kumar; Neupane, Uttam (International Journal on Engineering Technology and Infrastructure Development, 2024)
Payment has been an issue of major concern in the construction industry and most contractors reported that they have gone through late payment situations in government-funded projects. The issue of delayed payment in the construction industry is a global phenomenon. The objective of this research is to analyze the payment delays in the Department of Road, Road Division Surkhet construction projects. Altogether there are 61 projects under construction. Each representative from the contractor and all engineers from the Employer are selected as respondents. The Cronbach's alpha test was run, and the overall alpha value was found to be 0.978. The employer’s topmost rank is ‘unavailability of the budget under cause attributable to the employer, contractors' failure to understand the contract agreement under causes attributable to the contractor, and differing site conditions under causes beyond the party’s control. In contrast, the contractor ranks the topmost cause as unavailability of the budget, contractors' failure to follow certain procedures in a claim, and price escalation of the major construction materials respectively. The view of the employer emphasized that the delay in payment brings significant effects on the delay in project progress and creates cash flow problems for contractors with the value. Whereas contractors emphasized that the delay in payment creates cash flow problems for contractors. The employer has suggested that the contractor submit the latest progress work invoicing with adequate documents while asking for the payment to reduce the delay time in payment. In contrast, the contractor has suggested that both parties should understand the terms or clauses of payment in the project. The combined view of employer and contractor emphasized that Both parties should understand and should compel the terms or clauses of payment in the project to reduce the delay in the payment. The Hypothesis test also showed that there is a significant difference between the view of employer and contractor on the causes, effects, and possible solutions to reduce delay in the payment.